Scientific Observations on the Object of Crimes in the Customs Field (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes the object of customs crimes. In this case, the object of the crime is considered to be social relations, and the objects of crime are traditionally classified according to “vertical” and “horizontal” directions. The article uses a four-level system for classifying objects of crimes in the customs sphere, according to the “vertical” classification, that is, the method of dividing crimes into general, special, similar and direct objects, according to the “horizontal” classification into directly basic, directly additional and directly optional objects. In particular, it is noted that relations protected by criminal law are defined in Article 2 of the Criminal Code of the Republic of Uzbekistan as a general object of crimes in the customs sphere. Also, a special object of the crime is public relations that ensure human rights and freedoms in crimes provided for in Articles 130 and 1301 of the Criminal Code, social relations in the economic sphere in crimes provided for in Articles 182 and 184 of the Criminal Code, public relations that ensure security and public order in public crimes, provided for in Articles 2443, 2444, 246 and 2501 of the Criminal Code. In addition, social relations that ensure normal moral values in crimes provided for in Articles 130 and 1301 of the Criminal Code, social relations that protect the foundations of the economy in crimes provided for in Articles 182 and 184 of the Criminal Code, Articles 2443, 2444, 246 and 2501 of the Criminal Code as a generic object of the crime. It is determined that social relations that protect public safety are recognized as crimes. The article also analyzes the immediate main and direct additional objects of each crime in the customs sphere, and also draws conclusions for each case. At the same time, current criminal law norms, other legal documents, opinions of scientists and provisions of decisions of the Plenum of the Supreme Court of the Republic of Uzbekistan, as well as the author’s conclusions and opinions on each case are carefully analyzed.